Efficacy of intravenous induction of general anesthesia at BC Children’s Hospital – a prospective audit and identification of factors for success - Celine Hügel (Hochschule für angewandte Wissenschaften Hamburg, 2019)
The anesthesia department at BCCH, a tertiary pediatric centre in Vancouver, Canada, conducts IV cannulation for induction of anesthesia in awake children as an institutional policy, predominantly without anxiolytic premedication. An observational study of IV cannulation success in the operating rooms of BCCH was conducted over a one-month period at regular operating room capacity. The primary outcome was to identify the success rate of IV cannula placement in awake children in 2 attempts. For each case, basic demographic information, details about the setting in which the IV cannulation was performed, IV insertion characteristics, distraction techniques, behavior of the child, number of insertion attempts and success/failure were captured. Additionally, attending anesthesiologists and procedural suite nurses participated in semi-structured interviews to document key facilitators ensuring success of the IV cannulation attempt, barriers, effective distraction techniques, and teaching approaches. Data from 984 cases were summarized and plotted in MATLAB. A logistic regression model for successful IV inductions was designed and reduced using the Akaike information criterion optimization in R. The local BCCH IV induction bundle was successful in 90% of patients who required cannulation for planned IV induction. A majority of 90% had no or only minimal reaction to IV insertion; completely painand reaction-free IV insertion was achieved in 64 %. Predictors for success included older age of the pediatric patient and their behaviour at first encounter. Qualitative interview data of 13 participants were analyzed using a thematic approach in NVivo. Analysis of interview data was conducted in four phases: organizing, coding, categorizing, and theme development. Several factors for success were identified, inter alia effective distraction, preparation of the family to expect IV induction, effective use of local analgesic ream, and selectivity in consideration of IV induction appropriateness. Barriers included needle phobia, anxious or uncooperative parents, ineffective use of analgesic cream, and unfavourable anatomy. Distraction techniques highly depended on the age and developmental stage of the patient. Participants advised novices to practice on adults and sleeping children first, before attempting an IV start in an awake child. Results suggest that IV induction of anesthesia for a large majority of patients is feasible, when implemented as an institutional strategy. Results of this study further show that IV induction is possible without unduly traumatizing pediatric patients.